Physical activity, affirmation, and bullying in underserved youth - Vallender, Tyler (Kansas State University, 2024)
Introduction: Sexual and gender minority (SGM) youth have mental and physical health outcome disparities compared to their non-SGM counterparts. There is a volatile political and social environment based on their identities where SGM youth can face ridicule and bullying from peers at school. This ridicule can lead to lower physical activity levels, maladaptive eating habits, and increased risk of depression and suicidality. This study’s intent is to better understand SGM youth physical activity behavior and test if having an affirming or rejecting environment influences physical activity participation. Methods: The survey is an adapted form of the LGBTQ+ National Teen Survey by Watson et al. The study measured demographics, physical activity and sport participation, peer harassment, family acceptance and family rejection. The study was conducted as an electronic survey with respondents from an after-school SGM youth program. A youth advocate was used to ensure safety and anonymity of respondents. Results: There were 20 respondents (4 cisgendered boys, 7 transgender boys, 0 cisgender girls, 2 transgender girls, 4 gender non-conforming, and 3 with a different identity). Orientation had 6 bisexual, 6 queer, 4 asexual, 2 gay or lesbian, 1 still figuring out their identity and 1 something other than these. For physical activity participation, 2 had met CDC recommendations of 60 minutes of MVPA per day and 9 had never played on a school sports team. 8 were harassed for their gender, sexuality or how masculine or feminine they were. Six heard their caregivers tell them they were proud of them for their identity and 11 had their caregivers ridicule them for their identity. Conclusion: SGM youth are not meeting CDC guidelines and there is a volatile environment around these youth. Greater efforts for inclusion are needed at home and at school sports teams. Parents need education to support their SGM youth.
Keywords: Youth; Physical activity; Sexual and gender minority; Bullying